ANALISIS TEKHNIK PENGAJARAN QAWA’ID - DEVY AISYAH (Ta'dib, 2013)
In teaching ‘qawaid’, it needs an actual and an innovative strategy. A ‘qawaid’ teaching technique (uslub) is one of many teaching techniques of language. The choosing technique has to be consistent with teaching method used, and it has to be appropriate with relevant approaches. The application of teaching ‘qawait’ can be combined with some strategies. It means that if a teacher is not successful in applying one technique, s/he can change it with another technique directly. The differences of students’ mastery (not homogen) in class may influence the accuracy and the success of teaching technique used. The analysis of  representative ‘qawaid’ teaching technique for College Islamic Studies is that teaching ‘qawaid’ relys on the basis of Qur’an in which students can learn by applying ‘qawaid’ theory and also can master the content of Qur’an. Kata kunci: analisis, teknik pengajaran, qawa’id